Neoadjuvant chemotherapy followed by definitive local treatment in locally advanced sinonasal squamous cell carcinoma - Kim, Jina; Hong, Min Hee; Kim, Hye Ryun; Lim, Sun Min; Kim, Chang Gon; Kim, Da Hee; Sim, Nam Suk; Hong, Hyun Jun; Koh, Yoon Woo; Kim, Se-Heon; Wee, Chan Woo; Lee, Chang Geol; et al. (Frontiers in Oncology, 2024)
BackgroundSinonasal squamous cell carcinoma (SCC) is a rare disease entity, comprising less than 5% of malignancies of the head and neck. While surgery is the primary treatment approach, neoadjuvant and adjuvant therapies play crucial roles in enhancing the prognosis of patients undergoing treatment with the goal of cure. In this study, we aimed to explore the treatment outcomes of neoadjuvant chemotherapy (NAC) in patients with locally advanced sinonasal SCC.MethodsMedical records of patients diagnosed of locally advanced (cT3-4b, N0-3) sinonasal SCC treated with a definitive aim between January 2005 and March 2023 were retrospectively reviewed. Patients were categorized into the following groups based on the initial treatment: NAC followed by surgery, NAC followed by concurrent chemoradiotherapy (CCRT), definitive CCRT, or upfront surgery. Initial treatment plan was decided by a multidisciplinary team. Primary endpoint was overall survival (OS) and objective response rate, and secondary endpoints were progression free survival (PFS), cumulative incidence of local and distant failures, and treatment-related toxicity. The treatment response was assessed according to the RECIST criteria.ResultsTotal 126 patients were included, and the median follow-up period was 25.6 months. The objective response rate to NAC was 48.2%. The subsequent resection rate was 70%, 42.9%, and 16.7% for patients with stage T3, T4a, and T4b disease, respectively. Two-year progression-free survival did not differ significantly between the NAC followed by surgery and upfront surgery groups (53.6% vs. 60.6%, P = 0.615) or between the NAC followed by CCRT and definitive CCRT groups (26.7% vs. 37.4%, P = 0.506).ConclusionNAC may be a valuable treatment option for patients with locally advanced sinonasal SCC, as it provides an opportunity for curative surgery and exhibits non-inferior oncological outcomes compared with upfront definitive local treatments.